Aristarkh Lentulov’s Workshops and Moscow Painting Tradition of the 1920s–1930s - Maria Makarova, Maria A. (Actual Problems of Theory and History of Art, 2016)
This article is the first study on Aristarkh Lentulov’s workshops in the Free State Art Studios, VKhUTEMAS (Higher Artistic and Technical Workshops) and Moscow Art Institute covering the period of the 1920s–1930s. The study is based on the memoirs of Lentulov’s contemporaries, archival documents (RGALI – Russian State Archive on Art and Literature; GA RF – The State Archive of Russian Federation). and students’ works from Moscow and regional museum collections.Post-revolutionary years were the time of the master’s intensive pedagogical practice. In 1918–1919, Lentulov was in charge of the First Free State Art Studios (SGKhM) as their official representative. He led a painting workshop in the First SGKhM and a theater painting workshop in the Second SGKhM. In 1920–1925, he was a professor of painting and the head of the Theater and Decorative Art section at VKhUTEMAS. In the 1930’s, he worked at Moscow Art Institute.The painter’s method which was shaping the tradition of “Moscow school of painting” is considered in relation to Lentulov’s avant-garde experiments of the 1910’s and in the context of the Knave of Diamonds group of the 1920s–1940s whose principles of painting he shared. The master’s influence marked his student’s works that showed interest in his “architectural” landscapes, cubist portraits, and so on. The Knave of Diamonds members paid particular attention to plein-air, the fundamental problems of painting with a special accent on coloring. Sharing his experience of a plein-air painter was another side of Lentulov’s teaching practice. The methodology and some other issues of plein-air painting were the subject to a discussion between Lentulov and his colleagues at Moscow Art Institute in the 1930’s. Aristarkh Lentulov’s contribution to the development of “Moscow school of painting” deserves further scrutiny.
Keywords: A. V. Lentulov; “The Knave of Diamonds”; Moscow school of paintin; Free State Art Studios; VKhUTEMAS; Moscow Art Institute